A SEBARAN AREA BERMAIN LUAR RUANGAN DI PEMUKIMAN PADAT HUNI SEKITAR KAWASAN KOMERSIAL : Indonesia - Atik Prihatiningrum; Panji Anom Ramawangsa; Debie Rizqoh; Eka Vuspa Sari (UNIB Press, 2026)
High density neighbourhood areas directly adjacent to commercial areas such as markets, commercial corridors, and malls are environments that face significant challenges in creating a child-friendly environment. This study aims to identify unplanned outdoor play areas as areas discovered or created by children and forms of adaptation to find outdoor play spaces around their neighborhoods. This study uses a qualitative research design to identify unplanned areas as areas discovered or created by children for play using direct observation methods, interviews and documentation are used to validate the involvement of children who play actively in their play locations. The results show that the distribution of planned and unplanned play areas in densely populated residential areas around commercial areas has a ratio of 1:7. Unplanned play areas are preferred and frequently visited by children based on ease of access, ease of supervision, ease of meeting and playing with friends, and the freedom to play with types of games that are mobile games with and without equipment. The distribution of unplanned play areas utilizes urban circulation and transition spaces for play areas with types of games that are adaptive, minimal in material and utilize the physical characteristics of the space. Children actively create temporary play areas by re-functionalizing space, marking territory and social negotiation.